Wellens’ syndrome and finding of multiple coronary cameral fistulae: Is it time to discard this term? - Ibarrola, Martin (Ann Noninvasive Electrocardiol, 2019)
Wellens’ syndrome refers to electrocardiographic (ECG) abnormalities in the precordial T‐wave segment, which are associated with critical stenosis of the proximal left anterior descending (LAD) coronary artery. According to medical literature, this ECG abnormality is of paramount importance because this syndrome represents a preinfarction stage of coronary artery disease; however, same ECG pattern can also be seen in other conditions. Coronary fistula occurs due to anomalous communications between a coronary artery and a cardiac chamber or other vessel in the vicinity of the heart. We report a case of multiple coronary artery fistulae to the left ventricle in a 74‐year‐old woman who had a 2‐year history of intermittent atypical chest pain and exercise dyspnea with positive criteria mimicking Wellens’ syndrome without coronary atherosclerosis.